Experimental Evaluation of Workability Compressive Strength and Freeze-Thaw Durability of Concrete Containing Expanded Clay Aggregates - Sara Bensalem; Mohamed Lyes Kamel Khouadjia; Kamel Abdou; Ahmed Abderraouf Belkadi; Oussama Kessal (Graduate Program of Syiah Kuala University, 2022)
The development of the building materials industry in Algeria and worldwide has opened up new commercial opportunities for waste recovery. Using recycled materials and natural resources such as expanded clay aggregates are increasingly seen as a solution for the future to meet the gap between production, consumption and environmental protection. The present study investigates the effect of expanded clay aggregate (ECA) on a concrete slump, porosity, softening coefficient, compressive strength, and Freeze-thaw durability. Tests were conducted according to Russian National State Standard (GOST) 10060-2012 of concrete mixtures with expanded clay aggregate (ECA). A total of 7 mixtures were prepared. One is considered a reference mixture based on limestone aggregates. The other six mixtures were prepared by replacing the limestone aggregates with expanded clay aggregates, using two substitution rates (15%, 30% by weight) and three aggregates sizes (Sand 0/4, Gravel 8/16, and 16/25) while maintaining the same w/b ratio. The results indicate that ECAs can be used for concrete production. Furthermore, concrete containing 30% ECA (0/4) has the best properties and is the most freeze-thaw resistant than the other mixtures with ECA.